Mental health of activists in Iraq - A. Al-Kaseer, Eman (International Journal of Psychosocial Rehabilitation, 2024)
Background: Iraq witnessed a new phenomenon, thousands of young demonstrates were flooding streets of Baghdad, chanting their poignant trademark slogan "nureedwaten". In Iraq, a little research was focusing on mental health. No published data on mental health of protestors. Objective: to comment on mental health of protestors. Methods: A total of 460 protestors from Tahrir square (center of Baghdad). Their age range 20-40 years giving male to female ratio of 2.28:1. The personnel team was at corners of the square. The variables of interest were emotional, social, psychological well-being in addition to demographic information. Results: Out of the total, 98 (21.3%) were flourished. No significant association between age and the flourishing (p=0.4). Sex was not associated with flourishing (p=0.08). The flourishing increased significantly with educational level (p=0.0001). Conclusion: Protesting as a collective action enhanced flourishing among Iraqi youths.